THE THINKER AND THE TRUTH: BRINGING SØREN KIERKEGAARD IN DISCUSSION WITH REFORMATIONAL PHILOSOPHY - Glas, Gerrit (Philosophia reformata, 2012)
In reformational philosophy engagement with Søren Kierkegaard never really did get off to a good start. The present contribution is meant to reintroduce Kierkegaard in reformational philosophical discussions by focusing on the question of truth. How does the thinker as thinker relate to truth and what is the role of the I-self relationship in the search for truth? As working hypothesis it is stated that Kierkegaard’s many subtle analyses of the I-self relation can enrich reformational philosophical thinking about truth, by raising awareness for the intricate intertwinement between the object (the ‘what’) and the attitude (the ‘how’) of thinking. First, the thesis of indirect communication in the work of some of Kierkegaard’s pseudonymous authors will be investigated, including the question how this thesis affects the search for truth. Second, this thesis is compared with central concepts in reformational thinking, such as the heart, directedness at the Origin, and selfknowledge. Third, a brief review will be given of Climacus’ famous thesis that truth is subjectivity. After this review, the focus finally again shifts toward reformational philosophy, especially the way it has dealt with the religious dynamic in theoretical thought. It is concluded that there are differences in style, emphasis and conceptual ‘framing’ between Kierkegaard and Dooyeweerd, but that there are also many similar concerns and philosophical intuitions, more even than have been acknowledged so far in the literature. Kierkegaardian thinking is helpful in raising awareness of the tensions, ambiguities, and brokenness of our existence, even in the search for truth.